MENCIPTAKAN PEMBELAJARAN YANG EFEKTIF - Daulae, Tatta Herawati (AIN Padangsidimpuan, 2014)
AbstractLearning is an effort which is intended, aimed to control. So that we teach relative things to remain others. This effort can be done] by someone or a team owning interest and ability in designing and developing source learn which is needed. In execution of study has to be labored so that effective in creating study. Affectivity has some indicators for example, organization of better study, effective communications, and domination of enthusiasm in study, positive attitude to result appropriate student.Keywords: Learning and Effective